Detection of anti-Giardia lamblia serum antibody among children of day care centers - Semíramis Guimarães; Maria Inês L Sogayar
OBJETIVES: To detect anti-Giardia lamblia serum antibodies in healthy children attending public day care centers and to assess serological tests as tools for estimating the prevalence of G. lamblia in endemic areas. METHODS: Three separate stool specimens and filter paper blood samples were collected from 147 children ranging from 0 to 6 years old. Each stool sample was processed using spontaneous sedimentation and zinc sulfate flotation methods. Blood samples were tested by indirect immunofluorescence (IIF) and enzyme-linked immunosorbent assay (ELISA) for Giardia IgG. RESULTS AND CONCLUSIONS: Of 147 individuals tested, 93 (63.3%) showed Giardia cysts in their feces. Using IIF and ELISA, serum antibodies were detected in 93 (63.3%) and 100 (68%) samples , respectively. Sensitivity of IIF and ELISA was 82% and 72%, respectively. However, ELISA revealed to be less specific (39%) than IIF (70%). IIF also showed a higher concordance with microscopic examination than ELISA.